From business school dean to university president: leadership lessons from Dr Judy Olian - Robert M. Yawson (Organization Management Journal)
Purpose – This study aims to explore Dr Judy Olian’s leadership journey from business school dean to university president, aiming to distill key lessons for aspiring higher education leaders. Design/methodology/approach – The research employs a multimethod qualitative approach, including a personal interview with Dr Olian, an analysis of a podcast featuring her insights, a review of her official university profile and the author’s lived experience as a faculty member under Dr Olian’s leadership. This semiethnographic approach is supplemented by a review of relevant literature on higher education leadership. Findings – The study reveals critical competencies for transitioning to university leadership, including strategic vision, change management skills, team-building abilities and external relationship management. It highlights the importance of seeking broadening experiences, developing financial acumen and cultivating resilience in leadership roles. The research also underscores the significance of shared governance and the ability to navigate diverse stakeholder relationships. Practical implications – The research provides valuable insights for business school deans and other academic leaders aspiring to university presidencies, offering strategies for professional development and leadership transition. Originality/value – This study offers a unique perspective on the transition from business school leadership to university presidency. It combines insider observations with Dr Olian’s reflections to provide a comprehensive view of the challenges and opportunities in higher education leadership.